2010
DOI: 10.1063/1.3437201
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of electromagnetic force in electromagnetic forming process of metal sheet

Abstract: Electromagnetic forming (EMF) is a forming process that relies on the inductive electromagnetic force to deform metallic workpiece at high speed. Calculation of the electromagnetic force is essential to understand the EMF process. However, accurate calculation requires complex numerical solution, in which the coupling between the electromagnetic process and the deformation of workpiece needs be considered. In this paper, an appropriate formula has been developed to calculate the electromagnetic force in metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A validation has shown there is not necessary to use a visual assignment of values from experimentally attained curves H-a. It is more advantageous to employ the accurate calculation of H-a values which is based on interactions between the inductor and its mirror image known from the theory of induction heating [11,12] and electromagnetic forming [19].…”
Section: Testing the Horizontal Inductor Of Rectangular Cross-sectionmentioning
confidence: 99%
“…A validation has shown there is not necessary to use a visual assignment of values from experimentally attained curves H-a. It is more advantageous to employ the accurate calculation of H-a values which is based on interactions between the inductor and its mirror image known from the theory of induction heating [11,12] and electromagnetic forming [19].…”
Section: Testing the Horizontal Inductor Of Rectangular Cross-sectionmentioning
confidence: 99%
“…This results in constants mutual inductances between the disk and coil, throughout the forming process. Since the electromagnetic force is very fast, this simplification is valid [6]. By neglecting the variations of the mutual inductances during the forming operation, the transient electrical problem can be separated in a RLC primary circuit coupled with n secondary RL…”
Section: Discretized Model and Simplificationsmentioning
confidence: 99%
“…We assume that the electromagnetic force duration is short compared with the whole deformation time, and the effect of the metal sheet displacement is less significant than other EMF conditions, such as tube compression and expansions. Besides that, it has been reported that most of the sheet deformation results from the inertia forces due to the pulse of electromagnetic force [6].…”
Section: Introductionmentioning
confidence: 99%
“…5 Since this pressure is all that matters in electromagnetic forming, the details of the field distribution appear to be little studied. An analytical model 6 of the magnetic field diffusion in the process of electromagnetic forming has been proposed recently. The solution is sought in form of decaying oscillations.…”
Section: Introductionmentioning
confidence: 99%